Increase in the number of consultations for early telarche and the subsequent diagnosis of early or early puberty in pediatric endocrinology in Alava, after the confinement suffered during the COVID-19 pandemic - Leyre Aurora Vilella San Martin; Ignacio Díez López; Amaia San Martín Orayen; Sandra Maeso Méndez; Ainhoa Sarasua Miranda (International Journal of Sexual and Reproductive Health Care - Peertechz Publications, 2023)
Introduction: Due to the COVID-19 pandemic and home confinement measures, many of our routines and daily habits have been both affected and modified. Have these factors conditioned a real increase in precocious (PP) and accelerated puberty (AP)? Objectives: This is an observational and retrospective study in which the incidence of medical consultations due to premature thelarche is compared between March to December 2019 and 2020. The medical consultations occurred in the Pediatric Endocrinology (PE) consultation of our hospital. Patients and methods: The analysis involved 75 cases of young girls consulted with premature thelarche in 2019 and 97 girls which were consulted in 2020. From each patient, different variables were analyzed, such as somatometry, hormones, eco, and treatment. Results: In 2019, 75 first visits of PE were due to premature thelarche in young girls (accounting for 2.46% of the total number of first visits carried out in Pediatrics Outpatient Clinics (POC) and 16.77% of PE first visits). However, in 2020, 97 first visits were due to PE (3.52% of the total first-time visits of OC and 23.3% in PE). It was found that in 2020 the number of first-time visits due to premature thelarche increased by 28% compared to 2019 (p: 0.0001 mean comparison). In 2019, out of the 75 consultations due to premature thelarche, 40% were diagnosed with an earlier physiological puberty. Conversely in 2020, out of the 97 consultations, 61.77% had normal physiological puberty. These figures represent an OR of 1.54 (p: 0.02 t Student for independent samples). It was evaluated whether the patients had experienced > 3kg weight gain above 6 months prior to the medical visit. In 2020, 31.57% of patients experienced weight gain, whereas 68.42% did not. In 2019 patients who experienced weight gain accounted for 12.16% and 87.83% did not experience significant weight gain (p: 0.01 t Student for independent samples). Conclusion: Our data demonstrates there has been an increase in the incidence of referrals from Primary Attention to Pediatric Endocrinology to examine advanced thelarche during the period of lockdown measures (2020), in addition to an increase in the number of diagnostics of PP and AP in young girls in our hospital when compared to figures for 2019. Furthermore, in 2020 there was a greater number of patients who experienced a weight gain increase 6 months prior to the medical consultations. We hypothesize that the lockdown inflicted sedentary lifestyles together with changes in dietary habits, promoting weight gain in patients. This effect could have caused a body fat mass increase in girls, suggesting a "trigger effect" in the activation of the gonadal axis, causing a rise in the number of early puberty cases. IRB: CIEC 01/2017.